Nanospheres as the delivery vehicle: novel application of Toxoplasma gondii ribosomal protein S2 in PLGA and chitosan nanospheres against acute toxoplasmosis - Qi, WeiYu; Yu, YouLi; Yang, ChenChen; Wang, XiaoJuan; Jiang, YuChen; Zhang, Li; Yu, ZhengQing (Frontiers in Immunology, 2024)
Toxoplasma gondii (T. gondii) is a zoonotic disease that poses great harm to humans and animals. So far, no effective T. gondii vaccine has been developed to provide fully protection against such parasites. Recently, numerous researches have focused on the use of poly-lactic-co-glycolic acid (PLGA) and chitosan (CS) for the vaccines against T. gondii infections. In this study, we employed PLGA and CS as the vehicles for T. gondii ribosome protein (TgRPS2) delivery. TgRPS2-PLGA and TgRPS2-CS nanospheres were synthesized by double emulsion solvent evaporation and ionic gelation technique as the nano vaccines. Before immunization in animals, the release efficacy and toxicity of the synthesized nanospheres were evaluated in vitro. Then, ICR mice were immunized intramuscularly, and immune protections of the synthesized nanospheres were assessed. The results showed that TgRPS2-PLGA and TgRPS2-CS nanospheres could induce higher levels of IgG and cytokines, activate dendritic cells, and promote the expression of histocompatibility complexes. The splenic lymphocyte proliferation and the enhancement in the proportion of CD4+ and CD8+ T lymphocytes were also observed in immunized animals. In addition, two types of nanospheres could significantly inhabit the replications of T. gondii in cardiac muscles and spleen tissues. All these obtained results in this study demonstrated that the TgRPS2 protein delivered by PLGA or CS nanospheres provided satisfactory immunoprotective effects in resisting T. gondii, and such formulations illustrated potential as prospective preventive agents for toxoplasmosis.